APPLICATION OF THE EXTRATERITORIAL PRINCIPLE IN CROSS-BORDER CYBER CRIME JURISDICTION RELATING TO PERSONAL DATA - Nopit Ernasari (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Abtsract